UPAYA MENINGKATKAN KEAKTIFAN BELAJAR DAN BERPIKIR KRITIS MATEMATIKA MELALUI METODE PEMBELAJARAN SNOWBALL THROWING PESERTA DIDIK KELAS IV SD NEGERI GEDONGKIWO KOTA YOGYAKARTA: Penelitian Tindakan Kelas - Feby Wijayanti; Danuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: 1) Determine the implementation of the Snowball Throwing learning method in the subject of Mathematics with numbered material. 2) Increase the learning activity of students through the Snowball Throwing learning method in the Mathematics subject of numbered numbers. 3) Increase the critical thinking of students through the Snowball Throwing learning method in the subject of Mathematics of numbered material. This research is a Class Action Research (PTK) with a Kemmis and Taggart spiral model consisting of four stages, namely Planning, Action, Observation, and Reflection. The research subjects were 20 students in grade IV of SD Negeri Gedongkiwo Yogyakarta. Data was collected through observation, questionnaires, tests and documentation, then analyzed quantitatively and qualitatively descriptive. The validity of the data is carried out by examining credibility using triangulation techniques. The results of the study showed a significant increase in the activeness of learning and critical thinking in mathematics using the Snowball Throwing method. In the aspect of learning implementation, the percentage increased from 64% (poor category) in the first cycle of the initial meeting. to 71% (quite good in the final meeting. In the second cycle of the initial meeting, the implementation increased to 88% (good) and reached 94% (very good) at the final meeting. The learning activity of students also increased, from pre-cycle by 51% (good), then increased in cycle I to 54% and 68% (good), and experienced an increase in meaning in cycle II to 77% and reached 89% (very good). The students' critical thinking skills also developed, as seen from the overall completeness of 40% of pre-cycle students who obtained an average score of KKM, increased in cycle 1 from 55% to 65%, and in cycle II from 75% to 90% with 18 students who obtained an average score of KKM.